THE EMPOWERMENT STRATEGIES OF VILLAGE-OWNED ENTERPRISES (BUMDES) TOWARDS SUSTAINABLE DEVELOPMENT IN KIRIG VILLAGE - Ali Fahmi, Noor; Ghofur Wibowo, Muhammad (Jurnal Istiqro, 2024)
BUMDes is a village-owned enterprise managed by the local community that aims to manage village potential so as to develop the village economy and increase village income sources. BUMDes of Kirig village is relatively new so there is still a need for efforts from the government and village officials to highlight the potential of the village. This research uses SWOT analysis tools with the aim of seeing the potential of Kirig village, so that it can map what opportunities and challenges the BUMDes will face. This research also uses canva business model analysis with the aim of mapping the aspects that must be considered by BUMDes in running a business. Based on the results of the SWOT model analysis and the canva business model, it is found that the BUMDes of Kirig village is still new so that there is no maximum result and it is found that there is no participation from the community so that the BUMDes has not maximized employment and has not been able to prosper the community.